Between Intentions and Implementations: English Teachers’ Lived Experiences Educating ASD Learners under DepEd’s Inclusive Program - Christian Paul De Loyola; Shienna Marie Caparas (International Journal on Integrated Education, 2026)
Everyone, despite their differences, has the right to learn, and no disability should hinder a learner from maximizing their full potential through quality education. Delving into the lived experiences of general education English teachers handling secondary learners with Autism Spectrum Disorder (ASD) at Pulo National High School in Division of Cabuyao addressed the gap between the specialized needs of ASD learners—given the deficiencies in their social communication and behavioral functioning—and the limited training of general education English teachers, who are primarily equipped to teach language-related skills. While existing literature largely focuses on the experiences of ASD learners, there is a lack of studies examining these challenges from the perspective of teachers, specifically through the lenses of English language educators as to how they manage, strategize, and communicate with ASD learners within the general education classroom. This study aimed to understand how general education English teachers navigate inclusive classroom settings involving ASD learners. Using a qualitative phenomenological approach, Colaizzi’s method was employed to analyze data gathered through semi-structured interviews with seven participants. Findings revealed that the teachers had not received sufficient or intensive training to effectively support ASD learners, resulting in instructional and emotional challenges. The study concludes that while inclusive education programs by the Department of Education (DepEd) are well-intentioned, their implementation remains inadequate. Further, the results highlight instructional and behavioral challenges; policy-driven but practice limited training; need for comprehensive, systemic, and multi-level support; and balancing equity, sensitivity, and pacing in inclusive English classrooms.